The factors affecting the redisplacement in distal radius fractures - Tarlacık, Ali Okan; Kavak, Mustafa; Özçelik, Abdurrahman (The European Research Journal, 2022)
Objectives: Many instability criteria have been described in the literature to predict loss of reduction in distal radius fractures. However, the effect of the column location of the fracture on loss of reduction has not been investigated. The aim of this study is to investigate the effect of fracture column location and other radiological parameters on the loss of reduction of the distal radius fractures. Methods: A total of 106 patients who were treated conservatively for displaced distal radius fractures were included in the study. The average age of the patients included in the study is 54.9 years (range: 18-91 years). Anteroposterior and lateral radiographs of the wrist were taken in each patient at the time of first admission, immediately after reduction and casting, and at the 1st, 2nd and 6th weeks. Intraarticular fracture were evaluated by computed tomography (CT). Radial length, volar tilt angle and column location of the fracture were obtained by evaluating the radiographs and CT. The effects of post-reduction radiological parameters and column location of the fracture on loss of reduction were analyzed. Results: Reduction loss was detected in 23 (21.7%) of 106 patients. Metaphyseal fracture in 83 (78.3%) patients, intermediate volar column fracture in 76 (71.7%) patients, intermediate dorsal column fracture in 86 (81.1%) patients, ulnar column fracture in 52 (49.1%) patients and radial column fracture in 25 (23.6%) patients were determined. It was observed that having a fracture in the ulnar column or radial column caused a significant loss in radial length (p < 0.05). Metaphyseal and the intermediate column fractures did not make a statistically significant difference in reduction loss. Conclusions: Column location of the fracture can also be used to predict loss of reduction in the conservative treatment of distal radius fractures.